Sobre alguns casos de carcinoma primitivo do pulmão, do bronchio e da trachéa - C. Magarinos Torres; A. Penna de Azevedo (Memorias do Instituto Oswaldo Cruz, 1927)
1-Out of 1531 autopsies at Rio de Janeiro, Brazil, recorded in the Section of Pathology of «Instituto OSWALDO CRUZ», we found three cases of primary carcinoma of the lung, which gives the incidence of 0,195 per cent. They were not associated with tuberculos's and anthracos's was not marked. 2-The gross and microscopical features indicate that they are in reality primary cancers of the larger bronchi arising probably, from the bronchial lining epithelium. There is a striking similarity both macro and microscopical in Cases I and II, where the structure is that of cylindrical cell alveolar carcinoma. Mucus formation was never a prominent feature in these tumors. As in HENRICI's case they apparently invade the lung along the alveolar wall in more or less considerable extension retaining the alveolar septa as stroma. In case III the structure is that of squamous cell carcinoma, and the tumor mass, usually ulcerating, lies in the immediate vicinity of the bronchi, the extension to the lung tissue being not widespread. 3-Cases IV and V are tumors of the lower and median portion of the trachéa, squamous cell carcinoma in structure, which form marked contrast with the tumors originating in the larger bronchi: the tumor process never invades the lung parenchyma by continuous extension. In Case V extension to the mediastinal lymph-nodes is observed, and a tumor of the size of an orange is found in the anterior mediastinum: that tumor mass and the upper lobe of the right lung were only adherent by fibrous tissue of inflammatory origin and the tumor did not extend into the lung tissue.